Greening through trade how American trade policy is linked to environmental protection abroad - Jinnah, Sikina 1977-; Morin, Jean-Frédéric (The MIT Press, 2020)
"Trade-environment scholarship has long been focused on the World Trade Organization (WTO). However, against the backdrop of stalled WTO negotiations, the focus of trade-environment politics is shifting dramatically. In the WTO's shadow, the U.S. has increasingly pursued its environmental interests by incorporating far-reaching environmental provisions into bilateral and regional trade agreements. Importantly, the U.S. is now using these bilateral and regional trade agreements as a mechanism to force trading partner nations to implement seemingly tangential multilateral environmental agreements (MEAs), and to catalyze their adoption of new environmental norms and policies. This raises a slough of questions related to, for example, the process through which the U.S. identifies environmental issues to pursue through trade agreements, the character and extent of environmental norm and policy diffusion through trade agreements, and the impact these policies are having, if any, on MEA implementation and effectiveness. This book explores these questions. Centrally, this book asks: What are the impacts of the environmental provisions in US PTAs on environmental policy in trading partner nations and on the effectiveness of MEAs? We illuminate answers to these questions through a series of case studies. We argue that US trade agreements serve as mechanisms to diffuse environmental policies and norms to both trading partner nations and third party countries. Further, we argue that environmental provisions in US PTAs can play an important role in enhancing the effectiveness of MEAs, by strengthening the enforcement capacity of the latter through linkages to PTA dispute settlement systems."